The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.9775/kvfd.2013.10364
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin Resistance in Staphylococcus pseudintermedius Isolated from Shelter Dogs in Turkey

Abstract: SummaryStaphylococcus pseudintermedius is a recently described species of staphylococci that is frequently isolated from dogs. The increase in antimicrobial resistance in staphylococci and transfer of S. pseudintermedius from infected pets to humans threaten the public health worldwide. In this study, it was aimed to determine the prevalence of S. pseudintermedius from skin infections of dogs and to determine the prevalence of methicillin-resistance in S. pseudintermedius isolates by phenotypic and genotypic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
1
2
Order By: Relevance
“…The frequency of MRSP strains in this study was lower than in Asia but higher than in Europe. The rate of MRSP isolates in the present study was also lower than in a previous study in Turkey (Sareyyupoglu et al 2014), who reported S. pseudintermedius frequencies of 33.3% in shelter dogs with dermatitis. In the present study, 18 isolates were MRSP (29.5%).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The frequency of MRSP strains in this study was lower than in Asia but higher than in Europe. The rate of MRSP isolates in the present study was also lower than in a previous study in Turkey (Sareyyupoglu et al 2014), who reported S. pseudintermedius frequencies of 33.3% in shelter dogs with dermatitis. In the present study, 18 isolates were MRSP (29.5%).…”
Section: Discussioncontrasting
confidence: 89%
“…Although the comparison between different studies cannot be made easily due to the differences in the geographical region, sample type, and identification methods, these results indicate that S. pseudintermedius is the major causative agent of canine skin infections. In Turkey, the rate of S. pseudintermedius based on RFLP was 82.2% in healthy dogs and 80.4% in dogs with skin infections (Sareyyupoglu et al 2014;Findik et al 2018). Ozturk et al (2010) identified Staphylococcus species in dogs with otitis externa, skin wounds and pyoderma.…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte insanlarda ve hayvanlarda çoklu antibiyotik direncine sahip stafilokokların izole edilmesine dair birçok çalışma mevcuttur [4,7,22]. Özellikle metisilin dirençli Staphylococcus aureus (MRSA), metisilin dirençli Staphylococcus pseudintermedius (MRSP) ve metisilin dirençli koagülaz negatif Staphylococcus (MRCNS) türleri önemli infeksiyonlara yol açarken hayvanlar ve insanlar arasındaki taşıyıcılığı da önemli bir risk halini almıştır [1,25,26].…”
Section: Introductionunclassified
“…S. pseudintermedius sağlıklı köpeklerin %90'ından izole edilebilir ve deri infeksiyonlarının (piyoderma, dermatitis vb.) altta yatan nedenlerinden biri olarak karşımıza çıkmaktadır [9,13,26]. Kawakami ve ark.…”
Section: Introductionunclassified